2022
DOI: 10.1021/acs.langmuir.2c00482
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Cationic Structure on the Adsorption Performance of Ionic Polymers toward Au(III): an Experimental and DFT Study

Abstract: Ionic polymers have been proven to be promising adsorbents in recovering Au(III) due to their advantages of simple synthesis and high adsorption efficiency. However, the unclarity of the relationship between the adsorption ability of ionic polymers and their cationic structures hinders further optimization of their adsorption performance. This study synthesized a series of ionic polymers with pyridinium, imidazolium, piperidinium, pyrrolidinium, and triethylammonium cations to discover the effects of the catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…In other words, the positive charges of pyrrolidinium cations increase and the maximum ESP increases. It can be speculated that the extraction performance roughly follows the order of ESP. , As expected, [Pyr-EA]­[NTf 2 ] has the largest ESP and the highest extraction efficiency. However, the ESP of [Pyr-C 2 OC 2 ]­[NTf 2 ] is higher than that of [Pyr-Bu]­[NTf 2 ], but the extraction performance is worse than that of [Pyr-Bu]­[NTf 2 ], which does not conform to the order of ESP.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…In other words, the positive charges of pyrrolidinium cations increase and the maximum ESP increases. It can be speculated that the extraction performance roughly follows the order of ESP. , As expected, [Pyr-EA]­[NTf 2 ] has the largest ESP and the highest extraction efficiency. However, the ESP of [Pyr-C 2 OC 2 ]­[NTf 2 ] is higher than that of [Pyr-Bu]­[NTf 2 ], but the extraction performance is worse than that of [Pyr-Bu]­[NTf 2 ], which does not conform to the order of ESP.…”
Section: Resultssupporting
confidence: 58%
“…20 Kou et al reported that the adsorption performances of poly(ionic liquid)s (PILs) toward Pd(II) and Au(III) were affected by various N-substituents due to the changes of electrostatic potential (ESP). 21,22 As far as we know, no one has explained the influences of N-substituents on the extraction performances of pyrrolidinium-based ILs.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the pyrimidine inserted into the receptor was chosen precisely for this reason: being highly electron-poor, it has a marked tendency to form anion-π interactions, a characteristic confirmed by the crystal structures of several anion complexes with receptors containing this group [13][14][15][16][17]. Moreover, protonated pyridine groups have a non-negligible ability to form anion-π interactions [18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs) have been demonstrated to be superior candidates for supercapacitor electrolytes due to their beneficial electrochemical and physicochemical qualities of a wider working voltage window (3–5 V), better thermostability, lower volatility, and inflammability compared with organic or water electrolytes. Extensive investigations of the properties of EDLs in ILs with CNT electrodes have been carried out. Honda et al found that the tunable curvature of CNT may noticeably influence the EDL capacitance during experiments.…”
Section: Introductionmentioning
confidence: 99%